Gamma/delta T cells as cellular vehicles for anti-tumor immunity - Wang, Chelsia Qiuxia; Lim, Pei Yu; Tan, Andy Hee-Meng (Frontiers in Immunology, 2024)
Adoptive cellular immunotherapy as a new paradigm to treat cancers is exemplified by the FDA approval of six chimeric antigen receptor-T cell therapies targeting hematological malignancies in recent years. Conventional  T cells applied in these therapies have proven efficacy but are confined almost exclusively to autologous use. When infused into patients with mismatched human leukocyte antigen,  T cells recognize tissues of such patients as foreign and elicit devastating graft-versus-host disease. Therefore, one way to overcome this challenge is to use naturally allogeneic immune cell types, such as  T cells.  T cells occupy the interface between innate and adaptive immunity and possess the capacity to detect a wide variety of ligands on transformed host cells. In this article, we review the fundamental biology of  T cells, including their subtypes, expression of ligands, contrasting roles in and association with cancer prognosis or survival, as well as discuss the gaps in knowledge pertaining to this cell type which we currently endeavor to elucidate. In addition, we propose how to harness the unique properties of  T cells for cellular immunotherapy based on lessons gleaned from past clinical trials and provide an update on ongoing trials involving these cells. Lastly, we elaborate strategies that have been tested or can be explored to improve the antitumor activity and durability of  T cells in vivo.